KARAKTERISTIK PERTUMBUHAN DAN HASIL JAMUR MERANG (Volvariella volvacea L.) PADA MEDIA TANAM DAN KONSENTRASI PUPUK BIOGREEN YANG BERBEDA - Cut Nur Ichsan; Fuadi Harun; Nana Ariska (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
The objectives of this study were to evaluate characteristics of growth and yield of Volvariella volvacea L in different growing media and concentration of Biogreen fertilizer. Growing media consisted of rice straw and oil palm waste. Concentration of Biogreen fertilizer consisted of 0.5%, 1.0% and 1.5%. The result showed that rice straw gave better growth and yield of the mushroom but the highest production of the mushroom was at oil palm media. Concentration of Biogreen at level 1.5% gave better growth and yield of the mushroom. The best combination for fresh mushroom numbers was rice straw and concentration 5% Biogreen fertilizer but the best combination for mushroom yield was oil palm waste and concentration 5% Biogreen.